Alterations in core temperature during World Rugby Sevens Series tournaments in temperate and warm environments - Taylor, L.; Thornton, H. R.; Lumley. N.; Stevens, C. J. (European Journal of Sport Science, 2019)
Purpose: To characterize player core temperature (Tc) across two separate World Rugby Sevens Series (WRSS) tournaments in temperate and warm environments. Methods: Tc was collected in seventeen playing members of one men`s team competing at the Singapore (n = 12) and London (n = 11) WRSS tournaments. Exertional heat illness (EHI) symptoms, cooling strategy use, playing minutes and wet blub globe temperature (WBGT) were also collected. Linear mixed models and magnitude-based inferences assessed differences in Tc between all periods within-and between tournaments and were also used to assess the effect of WBGT and playing minutes on Tc. Results: Several players experienced Tc in excess of 38°C during warm-ups and 39°C during games. The highest mean Tc values were observed in the final game on all days and in Singapore Day Two, there were substantial game-on-game increases in mean Tc. These Tc responses were associated with playing minutes (effect size; ±90% CL = 0.38; ±0.20), although the effect of WBGT was trivial and unclear. Further, there were no differences in Tc between the two tournaments in the different environments. Despite high individual peak Tc values (Singapore 39.9°C; London 39.6°C); no signs/symptoms of EHI were reported, voluntary post-game cooling usage was minimal, and pre- and mid-cooling strategies were not implemented. Conclusions: During WRSS matches, peak Tc values approached thresholds associated with EHI (>40°C) and exceeded those demonstrated to reduce repeated sprint performance (>39°C). Practitioners may consider the use of compatible cooling and heat acclimation strategies to minimize Tc increase and maximize player preparedness and recovery.